Synthesis, Spectroscopic and Bactericidal Investigation of Some Transition Metal Complexes of Monomethyl phthalate - Rehman, Wajid; Hassan, Zonera; Shakir, Yasmeen (Asian Journal of Chemistry, 2012)
Seven novel transition metal complexes have been synthesized by using monomethyl phthalate as ligand and characterized through physical techniques such as melting point, elemental analyses, IR and 1H NMR spectroscopy. The complexes of Co(II), Ni(II), Fe(II), Zn(II), Mn(II) and hydrous and anhydrous Cu(II) exhibit trigonal bipyramidal and square planner geometry in solution state. It has been observed that monomethyl phthalate bound to the central metal atom through oxygen atom of the carboxylate group. The complexes formed were then treated with five different types of bacterial strains in order to check whether the synthesized compound is bioactive or not and the results were compared with the standard drug imipenem. Copper(II) complex showed highest inhibition zone against these microbes. The bactericidal activities indicated that metal complexes showed enhanced activity as compared to the free ligand.